Variabilidad de la frecuencia cardiaca en perros Braquicéfalos y Mesocéfalos (2022)
HRV through the use of the electrocardiogram gives us a broad indication of the health cardiovascular disease of our patients, which is important to evaluate whenever possible (Shaffer and Gisbert, 2017). Due to Regarding the information, this work is justified, since in canines there are certain anatomical peculiarities depending on the different types of skull, which cause dogs to exhibit different breathing patterns (deeper breaths in brachycephalic dogs), it is and is considered important to determine how much the increase in depth as a consequence of inspiratory effort in brachiocephalic breeds affects or the type of skull influences the parasympathetic tone and therefore the variability of the frequency (HRV)HRV, in dogs with different types of skulls, especially in those brachycephalic.